Komunikasi Organisasi Dalam Mempertahankan Talent Pada Andy Irawan Music - Handi, Esther Freya Angelica; Teguh, Monika (LPPM Stikosa - AWS, 2025)
In Indonesia, the orchestra business is rapidly growing. However, it is also facing difficult challenges, mainly in retaining talents. Andy Irawan Music is one of the orchestra businesses based in Semarang, Central Java, Indonesia. Andy Irawan Music specializes in high-end wedding events and has earned a reputation as a quality music service provider for mid-to-high-end clients. Andy Irawan Music faces typical issues in the creative industry such as talent turnover. This research shows how the organizational communication is implemented in Andy Irawan Music, to maintain its talents’ loyalty and improve performance quality. This research uses a qualitative approach with data collection through interviews and observations. The data analysis technique used in this research is the Miles and Huberman model data analysis technique which consists of data collection, data reduction, data display or presentation, and conclusions or verification. The results indicate that the use of top-down vertical, bottom-up vertical, and horizontal organizational communication strategies help to create a positive work environment, increasing a sense of belonging, and reducing talent turnovers. This research focuses on the role of structured organizational communication as an important factor in talent retention within the creative industry, especially in Andy Irawan Music, contributing to the overall sustainability and positivity of the work environment.